1991
DOI: 10.1029/91jb00640
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary meteoric hydrothermal systems and their relation to ore deposition, northwestern United States and southern British Columbia

Abstract: Tertiary meteoric hydrothermal systems have altered the rocks exposed over more than S% of the land surface of the northwestern United States and southern British Columbia, including at least 25,000 1m? in Idaho. The systems typically involved convective circulation of fluid derived from ordinary meteoric groundwater& around crystallizing, calc-alksline, epizonal plutons eiiiP.laced into coeval volcanic cover rocks.These individual systems had widely ranging "lifetimes" of 10' to 1Cf >:~and operated ~ocally th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…Our conclusion of brief activity at Round Mountain contrasts with a common interpretation that hydrothermal systems, even shallow epithermal systems, are long-lived, with life times of up to several million years (Silberman et al, 1979;Whalen et al, 1982;Silberman, 1985;Criss et al, 1991;Conrad et al, 1993). This is less of a contradiction than it first appears.…”
Section: Thermal Modelingcontrasting
confidence: 76%
“…Our conclusion of brief activity at Round Mountain contrasts with a common interpretation that hydrothermal systems, even shallow epithermal systems, are long-lived, with life times of up to several million years (Silberman et al, 1979;Whalen et al, 1982;Silberman, 1985;Criss et al, 1991;Conrad et al, 1993). This is less of a contradiction than it first appears.…”
Section: Thermal Modelingcontrasting
confidence: 76%
“…While this value is relatively high for purely surface-derived meteoric water, it is not uncommon in arid continental environments. In addition, the enrichment in 18 O may be related to hydrothermal fluid-rock interaction with the underlying basement, if the meteoric waters were heated to close to 100 • C (McKibbin et al, 1986;Criss et al, 1991;Rollinson, 1993). The validity of this result can be cross-checked using the quartz-water oxygen isotope fractionation.…”
Section: Hydrothermalism and Titanosaurian Reproductionmentioning
confidence: 99%
“…Beaty and Taylor 1982;Green et al 1983). Criss et al (1985Criss et al ( , 1991 found excellent spatial correlations between low δ 18 O-values and economic mineralization in siliceous rocks. Similar zonation around ore deposits in carbonate rocks have also been observed (e.g.…”
Section: Wall-rock Alterationmentioning
confidence: 82%
“…They exhibit great variations in size from relatively small intrusions (<100 km 2 ) to large plutonic complexes (>1000 km 2 ). Amongst the best documented examples are the Skaergaard intrusion in Greenland, the Tertiary intrusions of the Scottish Hebrides, and the Tertiary epizonal intrusions of the northwestern United States and southern British Columbia, where 5 % of the land surface has been altered by meteoric hydrothermal water (Criss et al 1991).…”
Section: Fossil Hydrothermal Systemsmentioning
confidence: 98%